Functional role and mechanisms of sialyllactose and other sialylated milk oligosaccharides. (14th May 2014) - ten Bruggencate, Sandra JM; Bovee‐Oudenhoven, Ingeborg MJ; Feitsma, Anouk L; van Hoffen, Els; Schoterman, Margriet HC
<x xml:space="preserve">Abstract</x> Human milk is a rich source of oligosaccharides. Acidic oligosaccharides, such as sialyllactose (SL), contain sialic acid (SA) residues. In human milk, approximately 73% of SA is bound to oligosaccharides, whereas only 3% is present in free form. Oligosaccharides are highly resistant to hydrolysis in the gastrointestinal tract. Only a small portion of the available oligosaccharides in breast milk is absorbed in the neonatal small intestine. SL and sialylated oligosaccharides are thought to have significant health benefits for the neonate, because of their roles in supporting resistance to pathogens, gut maturation, immune function, and cognitive development. The need for SA to allow proper development during the neonatal period is thought to exceed the endogenous synthesis. Therefore, these structures are important nutrients for the neonate. Based on the potential benefits, SL and sialylated oligosaccharides may be interesting components for application in infant nutrition. Once the hurdle of limited availability of these oligosaccharides has been overcome, their functionality can be explored in more detail, and supplementation of infant formula may become feasible.